ANALYSIS OF THE CORPORAL COMPOSITION; INDEX OF CORPORAL MASS (IMC); RCQ; AND HEART FREQUENCY OF INDIVIDUALS BOTH PRACTICING SEXES OF MUSCULAR ACTIVITY OF CLUBE S.E.R.A'S ACADEMY. OF THE MUNICIPAL DISTRICT OF ALTÔNIA - PR (Fiep Bulletin - online, 2015)
The objective of the present study was to analyze the adult apprentices' of muscular activity of both sexes corporal composition, with age group between 30 and 50 years. The study carcateriza-if I eat a traverse experimental research with quantitative approach. The group convenience amostral was composed by 30 muscular activity apprentices, being 15 women and 15 men, all volunteers (the), in the age group among 30 to 50 years of age; customers of Clube S.E.R.A'S academy (Sporting Society and Recreational Altoniense) of the municipal district of Altônia - PR. For the collection of data the following protocols were used:  In the statistical analysis of the work the "Test was used "t" of Students" for given pareados, having been adopted a level of significância of p
Keywords: Corporal composition; Muscular activity; Percentile of Fat; Thin Mass; Relação Cintura-Quadril; FC Repouso; Effort